Ignoring Gender-Based Immunometabolic Reprograming, a Risky Business in Immune-Based Precision Medicine - Vijay Kumar (Frontiers in Bioscience-Landmark)
Immunology advances have increased our understanding of autoimmune, auto-inflammatory, immunodeficiency, infectious, and other immune-mediated inflammatory diseases (IMIDs). Furthermore, evidence is growing for the immune involvement in aging, metabolic and neurodegenerative diseases, and different cancers. However, further research has indicated sex/gender-based immune differences, which further increase higher incidences of various autoimmune diseases (AIDs), such as systemic lupus erythematosus (SLE), myasthenia gravis, and rheumatoid arthritis (RA) in females. On the other hand, reproductive-age females also show a more potent immune response against infections and vaccines than their age-matched males—furthermore, some immune-based therapies, including immune checkpoint inhibitors (ICIs), show gender-based efficacy and adverse events. Metabolic demands are different in males and females. Immune cell function and polarization are also governed by their metabolic reprogramming, called immunometabolism and immunometabolic reprogramming (IR). Therefore, sex/gender-associated immune differences and their involvement in immune-mediated diseases and immune-based therapeutics indicate the demand for gender-based IR studies to increase the efficacy of immune-based precision medicine.